The Influence of Internal Control and Characteristics of Management Accounting Information Systems on Managerial Performance: Environmental Uncertainty as Moderating Variable - Zahra, Siti; Petra, Berta Agus; Suryadi, Dodi (UPI YPTK Journal of Business and Economics, 2025)
This study aims to determine the influence of internal control and Management Accounting Information Systems (MAIS) characteristics on managerial performance with environmental uncertainty as a moderating variable. In this study, the object used is PT Pelabuhan Indonesia This study aims to determine the influence of internal control and Management Accounting Information Systems (MAIS) characteristics on managerial performance with environmental uncertainty as a moderating variable. In this study, the object used is PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur. The sample was selected using a purposive sampling method with certain criteria needed in this study. The sample determination method used in this study was a total sampling of 30 people. The analysis technique in this study used the Structural Equation Modeling (SEM) technique with the Partial Least Squares (PLS) approach. The study's results prove that internal control has an insignificant influence on managerial performance. In contrast, the characteristics of the management accounting information system have a significant effect on managerial performance. Environmental uncertainty does not moderate the relationship between internal control and managerial performance. However, environmental uncertainty moderates the relationship between accounting information system characteristics and managerial performance. (Persero) Regional 2 Teluk Bayur. The sample was selected using a purposive sampling method with certain criteria needed in this study. The sample determination method used in this study was a total sampling of 30 people. The analysis technique in this study used the Structural Equation Modeling (SEM) technique with the Partial Least Squares (PLS) approach. The study's results prove that internal control has an insignificant influence on managerial performance. In contrast, the characteristics of the management accounting information system have a significant effect on managerial performance. Environmental uncertainty does not moderate the relationship between internal control and managerial performance. However, environmental uncertainty moderates the relationship between accounting information system characteristics and managerial performance.